2006
DOI: 10.3758/bf03193681
|View full text |Cite
|
Sign up to set email alerts
|

Why walkers slip: Shine is not a reliable cue for slippery ground

Abstract: In a series of four studies, we investigated the visual cues that walkers use to predict slippery ground surfaces and tested whether visual information is reliable for specifying low-friction conditions. In Study 1, 91% of participants surveyed responded that they would use shine to identify upcoming slippery ground. Studies 2-4 confirmed participants' reliance on shine to predict slip. Participants viewed ground surfaces varying in gloss, paint color, and viewing distance under indoor and outdoor lighting con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Previous work showed that observers erroneously base judgments about slip on visual cues such as surface color and shine (Joh, Adolph, Campbell, & Eppler, 2006). It is possible that the different feel-but similar appearance-of the low-and high-friction surfaces affected participants' perceptual judgments.…”
Section: Resultsmentioning
confidence: 88%
“…Previous work showed that observers erroneously base judgments about slip on visual cues such as surface color and shine (Joh, Adolph, Campbell, & Eppler, 2006). It is possible that the different feel-but similar appearance-of the low-and high-friction surfaces affected participants' perceptual judgments.…”
Section: Resultsmentioning
confidence: 88%
“…For instance, walkers rely on shine to predict slippery ground even though shine is not always a reliable visual cue for friction (Joh, Adolph, Campbell, & Eppler, 2006). Temperature is also a difficult variable to become attuned to.…”
Section: Perceiving Affordances That Lead To Risk Behaviorsmentioning
confidence: 99%
“…Joh et al (2006) reported that people rely on ‘shine’ information in forming judgements of slipperiness under dry conditions despite variations as a function of surface colour, viewing distance and lighting conditions. Lesch, Chang, and Chang (2008) asked participants to rate 38 different floor surfaces under dry conditions in terms of slipperiness, reflectiveness, light/dark, traction, texture and likelihood of slipping just by looking at them.…”
Section: Slipperiness Perceptionmentioning
confidence: 99%